Visual and Refractive Outcomes following Bilateral Implantation of Extended Range of Vision Intraocular Lens with Micromonovision - Sri Ganesh; Sheetal Brar; Archana Pawar; Kirti J. Relekar (Journal of Ophthalmology)
Purpose. To evaluate the outcomes following bilateral ERV intraocular lens implantation with micromonovision. Methods. 25 subjects underwent bilateral Tecnis Symfony IOL implantation with micromonovision. The dominant eye was targeted for emmetropia and the nondominant eye for myopia of −0.75 D. Uncorrected and corrected distance (UDVA, CDVA), intermediate (UIVA, CIVA), and near visual acuity (UNVA, DCNVA); reading performance; defocus curve; and contrast sensitivity were studied. Follow-ups were conducted at 1 week and 1 and 6 months postoperatively. Results. At 6 months postoperatively, the mean binocular UDVA, CDVA, UNVA, and DCNVA were −0.036 ± 0.09, −0.108 ± 0.07, 0.152 ± 0.11, and 0.216 ± 0.10 logMAR, respectively. Binocular UIVA and DCIVA were 0.048 ± 0.09 and 0.104 ± 0.08 logMAR, respectively, at 60 cm and −0.044 ± 0.09 and 0.012 ± 0.09 logMAR, respectively, at 80 cm. All patients had ≥0.2 logMAR UDVA and UNVA. Reading acuity and reading speeds showed improvement over time. Between defocus range of −2.50 and +1.00 D, the visual acuity remained ≥0.2 logMAR. Contrast sensitivity scores were within the normal range. 4 patients used reading glasses for very fine print. Conclusion. Bilateral ERV IOL implantation leads to excellent outcomes for far and intermediate vision, satisfactory outcomes for near vision, and good tolerance to micromonovision at the end of the 6 months. This trial is registered with CTRI/2015/10/006246.